Exchange rate volatility and financial performance of agriculture firms in Malaysia: an empirical analysis using GARCH, wavelet and system GMM - Md Reaz; Mahat, Fauziah; Dahir, Ahmed Mohamed; Sahabuddin, Mohammad; Al Mahi, Abu Saad Md Masnun (Prague Development Center, 2017)
The insurgence of exchange rate volatility over the years has gained the attention of not only scholars but also policy makers around the world. This paper investigates the influence of exchange rate volatility to the financial performance of agriculture firms in Malaysia. Authors use the system GMM dynamic panel techniques, wavelet coherence technique and GARCH (1, 1) for the period of 2001 and 2015. The findings show that the volatility of exchange rate of Malaysian Ringgit (RM) has a negative impact on the financial performance of agriculture firms in Malaysia. The ARME and AVA demonstrate a positive impact on the financial performance at 1% significance level for the full sample. The findings also reveal that financial performance, exchange rate, consumer price index, and interest rate comove while using the wavelet coherence.